Almost a hundred years later, the advertisement call of Aparasphenodon brunoi Miranda-Ribeiro 1920 (Anura: Hylidae) from the Atlantic Forest - Freire, Iasodhara Rodrigues; Thomassen, Hans; Rocha, Pedro Carvalho; Leite, Felipe Sá Fortes (Zootaxa, 2019)
The Neotropical genus Aparasphenodon Miranda-Ribeiro is composed of five recognized species commonly referred as “casque-headed frogs” (Frost 2018). Aparasphenodon brunoi Miranda-Ribeiro occurs in Atlantic Forest lowlands from the states of São Paulo to Bahia, Brazil (Feio et al. 1998; Mollo Neto & Teixeira Jr. 2012; Ruas et al. 2013). The biology of most Aparasphenodon species is poorly known. Within the genus, until now only Aparasphenodon arapapa Pimenta, Napoli & Haddad has its call formally described (Lourenço-de-Moraes et al., 2013, Forti et al., 2018, Guerra et al., 2018). Herein, we describe the advertisement call of Aparasphenodon brunoi Miranda-Ribeiro.